2012
DOI: 10.1073/pnas.1115396109
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment is associated with reduced volume in the hippocampal subfields CA3, dentate gyrus, and subiculum

Abstract: Childhood maltreatment or abuse is a major risk factor for mood, anxiety, substance abuse, psychotic, and personality disorders, and it is associated with reduced adult hippocampal volume, particularly on the left side. Translational studies show that the key consequences of stress exposure on the hippocampus are suppression of neurogenesis in the dentate gyrus (DG) and dendritic remodeling in the cornu ammonis (CA), particularly the CA3 subfield. The hypothesis that maltreatment is associated with volume redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
424
5
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(487 citation statements)
references
References 106 publications
(108 reference statements)
46
424
5
12
Order By: Relevance
“…Remarkably, this negative correlation remained significant even when accounting for group membership as a control variable in the whole-sample analysis, as it is also found in both groups separately. This is again well in line with previous reports demonstrating strong maltreatment effects on hippocampal volumes even if MDD patient status or life-time presence of affective disorders is accounted for (Chaney et al, 2014;Teicher et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Remarkably, this negative correlation remained significant even when accounting for group membership as a control variable in the whole-sample analysis, as it is also found in both groups separately. This is again well in line with previous reports demonstrating strong maltreatment effects on hippocampal volumes even if MDD patient status or life-time presence of affective disorders is accounted for (Chaney et al, 2014;Teicher et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…First, our finding of reduced hippocampal volumes in depressed patients compared with healthy controls is well in line with numerous imaging studies showing similar effects, including meta-analyses (Arnone et al, 2012a;Cole et al, 2011;MacQueen and Frodl, 2011). Second, the results of our study suggest a strong impact of childhood maltreatment on hippocampal morphometry in both, patients and healthy subjects, with comparable effect sizes in both samples (accounting for B8-9% variance of hippocampal volume), which is also in accordance with several previous studies reporting similar effects and effect sizes (Dannlowski et al, 2012;Edmiston et al, 2011;Teicher et al, 2012) but contradicts a study by Lenze et al (2008) that found childhood adversity to be associated with earlier onset of MDD but not with reduced hippocampal volume.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Stress-induced FC changes were calculated as the differences in FC strength between the stress and control conditions. Previous studies have associated ELS with reduced gray matter volume (GMV) in limbic areas (Teicher et al, 2012) and with personality traits, such as neuroticism, trait anxiety, and selfesteem (Grimm et al, 2014). We further explored the influence of GMV and personality traits on the main effect of EA, using ROI-based multiple regression model (main predictor: EA; covariates: age, IQ, experimental sequence, GMV in seed region, GMV in the corresponding ROI, neuroticism, trait anxiety, and self-esteem).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to trauma is particularly detrimental when it occurs in childhood or adolescence, disrupting numerous aspects of development in cognitive, emotional, and social domains, leading to adverse mental health and educational outcomes (Cicchetti & Toth, 1995; Koenen, Moffit, Caspi, Taylor, & Purcell, 2003) with long-term consequences for learning and memory (Teicher, Anderson, & Polcari, 2012), emotional functioning (De Bellis et al, 1994; McCrory et al, 2011; McLaughlin & Hatzenbuehler, 2009; Pollak & Sinha, 2002; Pollak, Vardi, Putzer Bechner, & Curtin, 2005), social relationships, elevated risk of re-victimization (Cole & Putnam, 1992; DiLillo, 2001; Follette, Polusney, Bechtle, & Naugle, 1996), and mental disorders (Kilpatrick et al, 2003; McLaughlin et al, 2012, 2013). …”
Section: Public Health Impact Of Traumamentioning
confidence: 99%